IMPLICATIONS OF PARENTING PATTERNS ON EARLY CHILDHOOD CHARACTER DEVELOPMENT IN BATU KELIANG HAMLET, CENTRAL LOMBOK - Azhari, Supian; Imama, Zakiyatul; Fadlillah, Azizah Nurul (Universitas Al-Hikmah Indonesia, 2024)
This study was conducted to determine the effect of parenting patterns on the development of early childhood character. This is based on the lack of parental attention to children. In order for children's characters to develop well, parents play an important role in providing care and education both in the early stages of life and after the child reaches adulthood. The purpose of this study was to determine the effect of parenting patterns on early childhood character education in Batu Keliang Hamlet, Central Lombok. Descriptive qualitative research was conducted to describe the results of research that had been conducted by the researcher. Data collection techniques used consisted of observation, interviews, and documentation with data sources, namely the community of Batu Keliang Hamlet, Pejanggik Village, Praya Tengah District, Central Lombok Regency, West Nusa Tenggara. While data analysis techniques consisted of data reduction, data presentation, drawing conclusions/verification. The following are the results of the study which show: (a) Parents in Batu Keliang Hamlet, Central Lombok, are suspected of having poor parenting patterns and paying less attention to the development of children's character in early childhood character education. (b) Environmental elements, both internal and external, have an influence on parenting patterns in early childhood character education. (c) The impact or implications of these parenting patterns on the character education of early childhood children result in bad character traits such as children lacking good manners, being lazy about going to school, and often saying dirty words or sentences.